Italian Unemployment 1975-1995 : An Analysis of Macroeconomic Shocks and Policies Using Evidence From a Structural Vector Autoregression - Christofides, Charalambos (IMF Working Papers; Working Paper, 1996)
This paper examines the determinants of Italian unemployment by estimating and utilizing a structural vector autoregressive (VAR) model. Both long-run and short-run macroeconomic determinants of unemployment are examined; the latter are analyzed in much greater detail than is customary in the literature. The relative contribution of long-run and short-run causes is quantified and the different time horizons over which they operate are identified. Policies affecting labor market performance are described and their effect estimated whenever data permit; policy implications are also drawn whenever possible. The most recent labor market reforms together with the atypical effects of the most recent recession are examined, and forecasts of unemployment are produced. A number of scenarios are also constructed to highlight the effect of alternative labor market arrangements.